2021
DOI: 10.3390/jcm10235468
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Keratitis—Review of Current Treatment Possibilities

Abstract: In many parts of the world, fungi are the predominant cause of infectious keratitis; among which, Fusarium is the most commonly isolated pathogen. The clinical management of this ophthalmic emergency is challenging. Due to the retardation of the first symptoms from an injury and the inability to differentiate fungal from bacterial infections based on clinical symptoms and difficult microbial diagnostics, proper treatment, in many cases, is postponed. Moreover, therapeutical options of Fusarium keratitis remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 138 publications
(150 reference statements)
2
22
0
15
Order By: Relevance
“…High MICs for antifungals are nee ded to treat Fusarium species in general, especially for VOR. This result was consistent in vitro studies as well as in vivo studies [28][29][30][31]. Other fungi, including Aspergillus and Candida species, are more susceptible than Fusarium species to azoles, particularly VOR [31].…”
Section: Bscva Outcomesupporting
confidence: 83%
“…High MICs for antifungals are nee ded to treat Fusarium species in general, especially for VOR. This result was consistent in vitro studies as well as in vivo studies [28][29][30][31]. Other fungi, including Aspergillus and Candida species, are more susceptible than Fusarium species to azoles, particularly VOR [31].…”
Section: Bscva Outcomesupporting
confidence: 83%
“…Some reports have shown that oral voriconazole was an effective treatment for FK 30,31 . Other studies also reported the success of intracameral amphotericin B administration and corneal collagen crosslinking (CXL) for the treatment of FK 2,4,19 . In our study, no patients underwent removal of the diseased eye, and all the patients had recovered by the time of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…large agricultural populations. If not properly treated, FK can lead to corneal destruction and endophthalmitis, with severe vision loss and even eyeball removal [1][2][3] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Natamycin and amphotericin B, bind to ergosterol, stabilize fungal cell membrane and contribute to inhibition of amino-acid and glucose membrane transport proteins. Voriconazole is used to block the cytochrome p450, which results in a reduction of the ergosterol concentration in the membrane and its destabilization (25). In the case of endophthalmitis, surgery is a basic requirement, with which surgery is performed for keratectomy and corneal transplantation or even enucleation of the eye (26).…”
Section: Difficult Treatmentmentioning
confidence: 99%